SOCIOLINGUISTIC LEARNING PRACTICE IN THE CONDITIONS OF DISTANCE LEARNING - Martos , Світлана (Journal of Information Technologies in Education (ITE), 2022)
The question of choosing modern methods and technologies, educational Internet services, ways of getting feedback from applicants for higher education during practical training in distance format remains relevant and insufficiently covered. The article presents the experience of implementing ICT in learning sociolinguistic practices in distance learning, which can be useful for science teachers of high school. The expediency and efficiency of the distance learning system "KSU Online" usage, created at Kherson State University on the basis of the information environment "Moodle", is proved. Various activities and resources of the platform allow students to place the necessary materials for practice and set up interaction between the head of the practice and higher education. It is known that Zoom platform is convenient to use for introductory and final conferences, group and individual consultations, online meetings. There is also identified the functional potential of the Viber messenger in distance learning: establishing a rapid and timely exchange of information between participants in the educational process, in particular, prompt counseling of interns on urgent issues. The effectiveness of using YouTube video hosting materials and involving students in creating their own media products (group video practice report of applicants on the Youtube channel of the Department of Ukrainian Philology and Journalism "PhiloVLOGiya") was demonstrated. The expediency of using multimedia posters created on the Thinglink platform as thematic collections of resources on the Internet to activate students' knowledge and direct them to study practice has been determined. Attention is drawn to the fact that there are various online services for the development and conduct the survey, the teacher just needs to advise students to use electronic resources that contain recommendations for the development and usage of online surveys